Impact of defensive team variables on goals conceded in the first division of the Spanish soccer league: a 10-year study - Prieto-González, Pablo; Martín, Víctor; Sal-de-Rellán, Alejandro (Biology of Sport, 2025)
This study aimed to analyse the influence of defensive team variables on goals conceded in the first division of the Spanish soccer league (LaLiga) between the 2013–2014 and 2022 2023 seasons. Defensive variables from LaLiga’s first division across ten seasons (2013 2014 to 2022–2023) were analysed, including all teams that participated during this period. Thirty three defensive metrics were selected from the Wyscout database, focusing on team performance. The selection process wasconducted by three independent researchers. Moderate positive correlations were found between goals conceded and opponents’ ball touches (r = 0.410), opponent ball possession ( r = 0.358), and opponents’ ball touches in various field areas (0.304 ≤ r ≤ 0.381). Defensive errors also correlated positively, while unsuccessful attempts to challenge a dribbling opponent showed a weak negative correlation. Regression analysis identified that opponents’ ball touches and shots conceded were the most significant factors, explaining 25.5% of the variance in goals conceded. The findings suggest that limiting opponents’ touches, possession, and shots is essential in minimizing goals conceded, as greater opponent control correlates with increased scoring chances. Defensive lapses undermine overall performance, while certain set-piece and defensive actions showed a limited effect. Developing strategies that reduce opponent control and improve challenge success rates is crucial. Further research is recommended across different leagues and categories to enhance understanding of defensive tactics in soccer